IT governance structures in Brazilian, Dutch and Portuguese universities - Bianchi, I. S.; Sousa, R. D.; Pereira, R.; Edimara Luciano (Procedia Computer Science, 2017)
Effective IT governance is determined by how the IT function is organized and where the IT decision-making authority is located within the organization. Three different IT governance structures may be considered: centralized, decentralized and federal. The appropriacy of these structures is based on the organization´s context. This article aims at analyzing how appropriate the IT governance structure adopted by universities is. Using a qualitative approach, we carried out six interviews in three countries, namely Portugal, the Netherlands and Brazil. The findings show that the centralized structure allows economizing on skills and applications, leading to cost reduction and standardization. While the decentralized mode calls for a duplication of resources, higher risks and a difficulty in communication in faculties, a centralized IT system emerges in the university. We can conclude that the federal structure is more suitable for universities where the infrastructure and strategy is centralized and the execution and operation are decentralized. Our findings are in consonance with the literature. This article will end presenting the limitations and future work.